Summertime actinic lichenoid eruption (SALE): an unusual presentation of lichen nitidus. - Jansen, T.; Romiti, R.; Herde, M.; Stücker, M.; Altmeyer, P. (European Journal of Pediatric Dermatology, 2001)
A 10-year-old Yugoslavian boy is reported who had a 2-year history of asymptomatic papular lesions on his face and neck. No Koebner phenomenon or involvement of oral mucosa, nails, scalp, or palms and soles could be observed. The eruption appeared during spring and summer, with complete remission during the winter. However, relapses occurred during subsequent summer seasons. Histopathological and immunohistochemical findings were consistent with a diagnosis of lichen nitidus. Treatment with 1% hydrocortisone cream once daily for two weeks and sun protection led to complete resolution of all skin lesions within two months. We concur with other authors that summertime actinic lichenoid eruption represents an unusual variant of lichen nitidus, best designated actinic lichen nitidus.